Comparison of Effect Efficiency and Voltage Regulation Between Three-Phase Transformer Winding Connections - Syamsyarief Baqaruzi; Surya Tarmizi Kasim (Indonesian Scientific Journal, 2020)
A transformer is an important device in electrical processes, as we know static electricity that involves magnetically coupled coils to increase or decrease the voltage. In three-phase transformer, there are various winding connections such as delta-delta (?, ?), wye-wye (Y, Y), wye-delta (Y, ?), delta-wye (?, Y), zig-zag (Z, Z), etc. And of the many often used connection are Yy0, Yd11, Dd0, and Dy5. From these various connections, each connection has different efficiency, losses, and voltage regulation. If they are connected with resistive, inductive, or capacitive loads. This paper method has discussed a transformer connection used are Yy0, Dd0, Yd11, and Dy5 in Laboratory Konversi Energi USU to see how the influence of load changes, on voltage regulation Where a state of balance load using are resistive, inductive, capacitive, and RLC combination. The result analysis of the experiment show, the best efficiency is at Dd0 connection, when loaded condition using capacitive is average 97.87%, and the best voltage regulation is obtained at Dy5, when loaded condition using resistive is average 28.35%